Testosterone synthesis in testicular Leydig cells after long-term exposure to a static electric field (SEF). (30th June 2021) - Di, Guoqing; Xiang, Junli; Dong, Li; Wu, Jiahong
Graphical abstract: Highlights: Long-term exposure of SEF damages the mitochondrial structure of Leydig cells. Long-term SEF exposure reduces the mRNA and protein of StAR, PBR, CYP11A1 in testes. Long-term SEF exposure inhibits testosterone synthesis in Leydig cells. Two mechanisms of testosterone synthesis inhibited by SEF exposure were analyzed. Abstract: China's clean energy and resources are mainly located in the west and north while electric load center is concentrated in the middle and east. Thus, these resources and energy need to be converted into electrical energy in situ and transported to electric load center through ultra-high voltage direct current (UHVDC) transmissions. China has built 25, 000 km UHVDC transmission lines of 800 kV and 1100 kV, near which the impact of electric field on health has attracted public attention. Previous studies showed that time-varying electromagnetic field exposure could disturb testosterone secretion. To study the effect of non-time-varying electric field caused by direct current transmission lines on testosterone synthesis, male ICR mice were continually (24 h/d) exposed to static electric field of 56.3 ± 1.4 kV/m. Results showed that on the 3 rd day of exposure and on the 7 th day after ceasing the exposure of 28 d, serum testosterone level and testicular oxidative stress indicators didn't change significantly. On the 28 th day of exposure, serum testosterone levels, testicular glutathione peroxidase (GSH-Px) activity, the mRNA and protein levels of testicular StAR, PBR, CYP11A1 decreased significantly, and testicular malondialdehyde (MDA) content increased significantly. Meanwhile, electron-dense edges and vacuolation appeared in lipid droplets of Leydig cells. The gap between inner mitochondrial membrane (IMM) and outer mitochondrial membrane (OMM) enlarged, which would cause the swelling of mitochondria, the rupture and deficiency of mitochondrial membranes. Analysis showed that testicular oxidative stress could induce the damage of mitochondrial structure in Leydig cells, which would decrease the rate of cholesterol transport from cytoplasm to mitochondria. Since cholesterol is the necessary precursor of testosterone synthesis, testosterone synthesis was inhibited. The decrease of the mRNA and protein expression levels of StAR and PBR in testes could diminish the cholesterol transported from OMM to IMM. The decrease of the mRNA and protein expression levels of CYP11A1 could reduce the pregnenolone required in testosterone synthesis and inhibit testosterone synthesis consequently.